One-month dual antiplatelet therapy followed by prasugrel monotherapy at a reduced dose: the 4D-ACS randomised trial - Jang, Youngwoo; Park, Sang-Don; Lee, Joon Pyo; Choi, Seong Huan; Kong, Min Gyu; Won, Yoon Sun; Kim, Minsu; Lee, Kyoung Hoon; Han, Seung Hwan; Kwon, Sung Woo; Suh, Jon; Kang, Woong Chol (EuroIntervention : journal of EuroPCR in collaboration with the Working Group on Interventional Cardiology of the European Society of Cardiology, 2025)
The efficacy and safety of a 1-month prasugrel-based dual antiplatelet therapy (DAPT) strategy followed by reduced-dose prasugrel monotherapy in acute coronary syndrome (ACS) patients treated with drug-coated stents (DCS) have not been studied. We aimed to evaluate the safety and efficacy of a 1-month prasugrel-based DAPT regimen followed by reduced-dose monotherapy in ACS patients receiving a DCS. In the multicentre, randomised, open-label trial, 656 ACS patients (age: 60.9±9.7 years; 82.6% male) receiving DCS were randomised to either 1-month DAPT with aspirin 100 mg and prasugrel 10 mg (or 5 mg in patients aged ≥75 years or body weight <60 kg) followed by prasugrel 5 mg monotherapy (1M-DAPT) or 12-month DAPT with aspirin and prasugrel 5 mg (12M-DAPT). The primary endpoint was 12-month net adverse clinical events (NACE), a composite of death, non-fatal myocardial infarction, stroke, ischaemia-driven target vessel revascularisation, and Bleeding Academic Research Consortium Type 2-5 bleeding. NACE occurred in 4.9% of the 1M-DAPT group and 8.8% of the 12M-DAPT group, meeting the criteria for both non-inferiority (non-inferiority margin: 2.0%; absolute difference: -3.9%; 95% confidence interval [CI] for absolute difference: -6.7% to -0.2%; p=0.014) and superiority (hazard ratio [HR] 0.51; 95% CI: 0.27-0.95; p=0.034). Any bleeding occurred in 1.2% vs 5.2% (HR 0.23; p=0.009), and major bleeding occurred in 0.6% vs 4.6% (HR 0.13; p=0.007) in the 1M-DAPT versus 12M-DAPT group, respectively. Ischaemic outcomes were similar. In ACS patients treated with DCS, a 1-month prasugrel-based DAPT strategy followed by prasugrel 5 mg monotherapy reduced NACE by 49%, mainly driven by a 77% reduction of bleeding events without compromising ischaemic safety.